2017
DOI: 10.1021/acs.jmedchem.7b01552
|View full text |Cite
|
Sign up to set email alerts
|

From Experiments to a Fast Easy-to-Use Computational Methodology to Predict Human Aldehyde Oxidase Selectivity and Metabolic Reactions

Abstract: Aldehyde oxidase (AOX) is a molibdo-flavoenzyme that has raised great interest in recent years, since its contribution in xenobiotic metabolism has not always been identified before clinical trials, with consequent negative effects on the fate of new potential drugs. The fundamental role of AOX in metabolizing xenobiotics is also due to the attempt of medicinal chemists to stabilize candidates toward cytochrome P450 activity, which increases the risk for new compounds to be susceptible to AOX nucleophile attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 51 publications
(113 reference statements)
0
34
0
Order By: Relevance
“…5. The meta-O-linked EDGs in XK-469 (2-[4-(7-chloroquinoxalin-2-yl) oxyphenoxy]propanoate) (Anderson et al, 2005;Hutzler et al, 2012) and VU0409106 [3-fluoro-N-(4-methyl-2-thiazolyl)-5-(5-pyrimidinyloxy) benzamide] (Morrison et al, 2012), or the meta-N-linked EDG in example 2, and compounds 20 (Lepri et al, 2017;Cruciani et al, 2018) and 30 (Glatthar et al, 2016) made these compounds more susceptible to AO metabolism (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…5. The meta-O-linked EDGs in XK-469 (2-[4-(7-chloroquinoxalin-2-yl) oxyphenoxy]propanoate) (Anderson et al, 2005;Hutzler et al, 2012) and VU0409106 [3-fluoro-N-(4-methyl-2-thiazolyl)-5-(5-pyrimidinyloxy) benzamide] (Morrison et al, 2012), or the meta-N-linked EDG in example 2, and compounds 20 (Lepri et al, 2017;Cruciani et al, 2018) and 30 (Glatthar et al, 2016) made these compounds more susceptible to AO metabolism (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…Future clinical studies would be needed to determine whether these interactions occur in vivo. To date, studies have been reported on AOX1 protein structure-drug metabolism relationships to predict human AOX1 substrates (Lepri et al, 2017;Cruciani et al, 2018), but limited information on human AOX1 structure-enzyme inhibitor relationships determined based on the crystal structure of human AOX1 (Takaoka et al, 2018;Deris-Abdolahpour et al, 2019). The molecular-docking approach developed in this study, by virtue of its consistent performance and the ability it allows for meaningful comparative analyses of chemical inhibitors, provides a robust in silico framework for future investigation of the binding of chemical inhibitors with AOX1.…”
Section: Discussionmentioning
confidence: 99%
“…The three-dimensional (3D) structures of the lowest energy conformations of the 5 lead candidates were used as input data in the MetaSite 6.0 program [47] (Molecular Discovery, Borehamwood, Hertfordshire-United Kingdom). For each compound, twenty constituents were generated by the program.…”
Section: Metabolic Predictionmentioning
confidence: 99%